Change Detection From Very-High-Spatial-Resolution Optical Remote Sensing Images: Methods, applications, and future directions - Wen, Dawei; Huang, Xin; Bovolo, Francesca; Li, Jiayi; Ke, Xinli; Zhang, Anlu; Benediktsson, Jon Atli (IEEE geoscience and remote sensing magazine, 2021)
Change detection is a vibrant area of research in remote sensing. Thanks to increases in the spatial resolution of remote sensing images, subtle changes at a finer geometrical scale can now be effectively detected. However, change detection from very-high-spatial-resolution (VHR) (≤5 m) remote sensing images is challenging due to limited spectral information, spectral variability, geometric distortion, and information loss. To address these challenges, many change detection algorithms have been developed. However, a comprehensive review of change detection in VHR images is lacking in the existing literature. This review aims to fill the gap and mainly includes three aspects: methods, applications, and future directions.